Copper-Catalyzed Tandem Dehydrocyanation and [3+2] Cycloaddition Reactions of Phenacylmalononitriles: Regioselective Synthesis of Functionalized 4-Benzoyl-5-cyanopyrazoles under Mild Conditions - Yavari, Issa; Khaledian, Omid (Synthesis, 2020)
A novel copper-catalyzed [3+2] cycloaddition reaction with concomitant in situ generation of benzoylacrylonitriles and nitrile imines from phenacylmalononitriles and hydrazonoyl chlorides, respectively, is reported. The reaction was performed using copper(I) chloride as catalyst and N-methylimidazole as a clean complexing agent/weak base to afford the functionalized 4-benzoyl-5-cyanopyrazoles in moderate to good yields and excellent regioselectivity under ambient conditions. This method provides rapid access to a wide range of highly functionalized 4-benzoyl-5-cyanopyrazoles.
Keywords: 4-benzoyl-5-cyanopyrazoles; copper catalysis; [3+2] cycloaddition; phenacylmalononitrile; hydrazonoyl chloride